Flow over Heated Terrain. Part II: Generation of Convective Precipitation - Tucker, Donna F.; Crook, N. Andrew (Monthly weather review, 2005)
Previous studies have shown that thunderstorms in the Rocky Mountain region have preferred areas in which to form. There has been some indication that these areas depend on the midtropospheric wind direction. A nonhydrostatic model with a terrain-following horizontal grid is employed to investigate the initiation of precipitating convection over heated topography. Horizontally homogeneous meteorological conditions with no directional shear in the vertical wind profile are used. The numerical simulations indicate that precipitating convection was more likely to be generated downwind of ridges than upwind of them. Initiation of these storms was more likely downwind of ridges with their long axis parallel to the wind direction than downwind of ridges with their long axis perpendicular to the wind direction. In Part I of this study it was shown that heating-induced convergence is larger downwind of a ridge with its longer axis parallel to the wind direction. For the orographic configuration of the Rocky Mountains, total precipitation is maximized for southerly and northwesterly winds. Slower wind speeds are more likely and faster wind speeds are less likely to produce convective storms. Soundings with larger instability are more likely to produce convection. The soundings with a greater temperature lapse rate produce more initiation locations, and soundings with greater moisture produce greater amounts of precipitation. Even though a number of assumptions were made for this study, the authors believe the results explain a significant amount of the observed variability in the initiation locations of precipitating convection in the Rocky Mountains during the summer. Because of the theoretical basis for this work, detailed in Part I of this study, the authors believe it should explain convective initiation in other mountainous areas that are subject to strong solar heating.